Pengaruh Persepsi Siswa pada Penggunaan Metode Pembelajaran Jigsaw pada Mata Pelajaran Ekonomi terhadap Hasil Belajar Siswa Kelas X IPS SMA Budhi Warman II Jakarta Timur - Yosiana Rut Suryaningsih (Neolectura, 2019)
This study aims to knows influence the perceptions of students on the use of jigsaw learning methods in Economic Subjects on the learning outcomes of Class X IPS students at Budhi Warman II High School in East Jakarta. The method used in this research is quantitative. The population in this study were students of class X IPS 1 and X IPS 3 at Budhi Warman II Senior High School. So that out of 115 IPS class X students, the researchers took a population of 75 students to be sampled from two classes. In the experimental class which numbered 40 students will be given material with a jigsaw learning model while the control class numbering 35 students will be given material with a conventional learning model. Data collection techniques by conducting field research are observation, tests containing questions or exercises or other tools used to measure skills, measurements, intelligence, abilities or talents possessed by individuals or groups, and library research, as well as documentation. The research instrument used was a multiple choice test consisting of 8 questions. Data analysis techniques used descriptive data analysis, including the mean, median mode, variance, and standard deviation and hypothesis testing. The results in this study indicate that there is an effect of the use of Jigsaw Learning Methods on Student Learning Outcomes in Economic Subjects in X grade IPS students and from the results of students' perceptions on the perception statement sheet of students in class X IPS expressing liking the jigsaw learning method in economic subjects at Budhi High School Warman II, East Jakarta 2019/2020 Academic Year.